(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Anglo-Indian writer, who started as a novelist in the1950s, and then in the mid-1960s began her successful career as a screenwriterwith the Ivory-Merchant film team. Jhabvala won her first Academy Awardfor A Room with a View (1985)for best adapted screenplay. The second came for Howards End (1992). Both films were based on E.M. Forster’snovels. Jhabvala’s novel Heat andDust was awarded the Booker Prize in 1975. "But I think Icould not have learned from films if I had not written all these novels andreally learned how to set characters in motion. If you just sit down and writea screenplay, I don’t think you can." (from Conversationswith Screenwriters by Susan Bullington Katz, 2000)